THE SENSE OF BELONGING: HYBRID OR REINVENTION? A STUDY OF K. S. MANIAM’S IN A FAR COUNTRY - Zanyar Kareem Abdul (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2021)
The issue of race, identity, and multiculturalism are focal points in modern novels. K. S. Maniam, as an Indian-Malaysian as such, explains the same question again in his writings. There is a longing or rather a forlorn look at India as the Motherland of some of the Indians in Malaysia in the setting of K. S. Maniam’s stories. The novel does not provide a complete recovery of the original country; it is instead giving a deep insight into finding out a connection to the place one settles in. In a Far Country  is a typical example of the modern chaotic world through which Maniam sheds light on it. The research aims to analyse the redefinition of identity and determining race. It is also to explore the choices between a native and nonnative value in a foreign land. Under the analysis, Homi Bahbah’s theory of hybridity is chosen for the study of the novel. It is a significant and difficult step at the same time to reinvent one’s identity through a hybrid culture or rather to be called “reinvented” when the final solution fails and instead “reinvention” shapes a new identity.